ANALIS PERTUMBUHAN EKONOMI DAN KETIMPANGAN ANTAR KABUPATEN HASIL PEMEKARAN WILAYAH INDRAGIRI (KABUPATEN INDRAGIRI HULU, KABUPATEN INDRAGIRI HILIR, KABUPATEN KUANTAN SINGINGI) - Riko Handoko Harahap; H.B. Isyandi; Eka Armas Pailis (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This research aims to determine the classification of economic growth and regionalchanges before and after autonomy in the area of Indragiri, Indragiri Hulu, IndragiriHilir and Kuantan Singingi regencies. The data used is secondary data compiledfrom publications or data published by BPS which includes the PDRB data ADHK1995-1999 and 2014-2018, population number 1995-1999 and 2014-2018. Theclassification between the districts is calculated using Tipologi Klassen, while forincome inequality is calculated using the Williamson index. The results of theanalysis using Tipologi Klassen at the time of 1995-1999 showed that the districtIndragiri Hulu entered the area forward, District Indragiri Hilir developed area butdepressed and Kabupaten Kuantan Singingi rapidly developing areas, while theresearch results in the period 2014-2018 showed that the district Indragiri Hilirentered into the category of developing areas rapidly, while the district Indragiri Huluand Kuantan Singingi Regency entered in the category of areas developed butdepressed which means in the period before the autonomy and after Region. As forthe results of the analysis using the Williamson index of districts in the Indragiriregion, the income gaps between the regions are low with the average of theWilliamsonnya index 0.07 for the period 1995-1999 and during the period 2014-2018or after the autonomy of the value of the Wiliamson index indicates the value of 0.09index which means that it is sufficiently low or evenly.